STUDI LITERATUR: ANALISIS LITERASI SAINS ERA SOCIETY 5.0 DI SEKOLAH DASAR - Awalina Barokah; Nunu nurhaliza; Bulan Kurniati; Torik Kaddafi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the achievement of scientific literacy in society 5.0 in elementary schools in terms of several aspects of content, process and context, the nature of science. This research method uses a literature study in which data is collected through sources used including articles, journals, documents, books and other literature studies. The results of this research explain the scientific literacy skills that students must have in facing the era of society 5.0 so that they can fulfill science skills, understand science, communicate science, and apply science to solve problems in everyday life.